Characterization and properties of palm kernel shell filled low density polyethylene biocomposites - Romisuhani, Ahmad (Universiti Malaysia Perlis (UniMAP), 2014)
Biocomposites based on palm kernel shell (PKS) and low density polyethylene (LDPE) was investigated. The biocomposites were prepared by using Z-Blade mixer at processing temperature 180 oC and rotor speed 50 rpm. The effect of filler loading of PKS as filler in LDPE on mechanical properties, water absorption, morphology, thermal properties and fourier tranformation infrared spectroscopy (FTIR) were studied. The results show that the increasing of filler loading have decreased the tensile strength and elongation at break but increased the Young’s modulus and water absorption. The morphology study using scanning electron microscopy (SEM) shows poor interfacial interaction between PKS and LDPE with increasing of the filler loading. The crystallinity of the biocomposites increased with increasing of PKS loading. To improve the mechanical properties, compatibilizer, Polyethylene co-acrylic acid (PEAA) was used. The effect of chemical modification of biocomposites with polyethylene co-acrylic acid (PEAA), acrylic acid (AA) and coconut coupling agent (COCA) enhanced the tensile strength, Young’s modulus and crystallinity of the biocomposites but reduced the elongation at break and water absorption. The morphology study (SEM) shows that the filler-matrix interaction was improved with incorporation of PEAA, AA and COCA. The FTIR results show that the wave number of hydroxyl group for all biocomposites shifted to lower wave number which indicates that interaction between the hydroxyl groups from PKS with compatibilizer and coupling agent.